DEVELOPMENT OF EXPANDED CLAY CONCRETE PRODUCTION TECHNOLOGIES BASED ON ADDITIVES - Abdurakhimov Abdukarim Abdukhalimzoda (American Journals Publishing, 2023)
It is not for nothing that the world community today includes only thermal energy in the most expensive energy class among the various categories of energy, because thermal energy, unlike other energies, does not change from one type to another, is not regenerated at all, it only burns and ends. It is for this reason that the countries of the European continent, which we recognize as developed, today prohibit the construction of a building or structure without the use of heat-insulating construction materials. In recent years, extensive measures have been implemented in our republic to further deepen economic reforms in the construction materials industry and to rapidly develop the network, to increase the production of new modern construction materials, structures and products, and to expand their types, and certain results are being achieved. The significant aspect of technical progress is that it is effective. is the loss of mass during the application of the material, in this situation it is necessary to send porous fillers to them.The use of lightweight concrete reduces the mass of the building structure by 35%, and cement by 10%. In this situation, the size of the structure increases, and its thermotechnical and acoustic properties are improved. In the last 10 years, a lot of research and studies have been carried out on the selection of composition, stability of lightweight concrete in porous aggregates.